Military Mapping, Philhellenic Geography, and the Making of Greece, 143 1811–1827 - Tolias, George (The Historical Review/La Revue Historique, 2023)
Through an investigation of the resources, the mapping practices, the reception as well the geographical concepts that lie behind a series of maps of Greece produced by the prestigious Dépôt de la Guerre during the Greek War of Independence, this article seeks to highlight the links between scientific culture and geographical imagination in the context of philhellenism and to explore the ideological and political function of cartography in the age of nationalism and technological positivism.